Предложения по организации системы динамического управления телекоммуникационными сетями - Овчинников, К. А. (ХНУРЭ, 2009)
The given work is devoted to the modernization of existing management systems by creation of flex system which will change its management architecture according to some situation in telecommunication network. The aim of this work is to define conditions (situations) which will cause switching
Keywords: управление телекоммуникационными сетями